TERM KECERDASAN DI DALAM AL QUR’AN - Amsori Amsori (Karimiyah: Journal of Islamic Literature and Muslim Society, 2021)
If we look at the analysis of the position of reason in Islam, then Islam really glorifies reason. While most people have the full spectrum of intelligence, individuals exhibit different cognitive traits. "Tadabbur is the attention of the heart through sight in noticing the result." Here will be described intelligence in the conception of the Qur'an. These three intelligences will have implications for other intelligences. Universal intelligence, intelligence that affects various aspects of human life. Understanding Intelligence Intelligence is rooted in the word 'intelligent' which in English is called intelligent, educated, shrewd, clever, mentally agile. It is Allah who introduces (instinct) through reason (himself)". So it is hoped that from here, a conception of intelligence is born in the conception of Islamic education which is based on the Qur'an. In the Qur'an more than 10 times its contents are about motivation to use reason, weigh, think, contemplate and others. In fact, in addition to the word at tafakkur (التفكّر) contained in the Qur'an (QS. The theories of intelligence above which even though they are called Spiritual Intelligence (SQ) are still built on a rational basis that gives birth to secularism. Then the prefix is ​​given ' ke' and the suffix 'an', becomes intelligence which in English is called 'intelligence'.